Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acssuschemeng.2c05261
|View full text |Cite
|
Sign up to set email alerts
|

Porous Cuboidal SrNbO2N Crystals Grown on a Nb Substrate as an Active Photoanode for Neutral Seawater Splitting under Sunlight

Abstract: Photoelectrochemical (PEC) water splitting using n-type SrNbO2N is beneficial for hydrogen production because its narrow-band-gap energy allows it to harvest visible light up to 700 nm. However, the oxygen evolution reaction (OER) activity of oxynitride at neutral pH is very limited, hindering its application to commercial PEC devices. Herein, we report enhanced seawater-splitting activity at neutral pH over porous cuboidal SrNbO2N crystals grown on a Nb substrate under simulated sunlight. The oxynitride photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The half water oxidation of water splitting typically exhibits very slow kinetics compared with half water reduction so that alternative oxidations using the oxynitrides have been addressed to boost water splitting and then produce H 2 gas with a higher evolution rate. 29 Recently, CO 2 reduction using these compounds has also been reported since carbon neutrality is becoming critical globally. 30,31 First, we discuss the various reactions that can be photocatalyzed by perovskite and layered perovskite oxynitrides under sunlight (or only visiblelight irradiation), the standard reduction potentials for which are reported in Table 1.…”
Section: Visible-light-driven Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The half water oxidation of water splitting typically exhibits very slow kinetics compared with half water reduction so that alternative oxidations using the oxynitrides have been addressed to boost water splitting and then produce H 2 gas with a higher evolution rate. 29 Recently, CO 2 reduction using these compounds has also been reported since carbon neutrality is becoming critical globally. 30,31 First, we discuss the various reactions that can be photocatalyzed by perovskite and layered perovskite oxynitrides under sunlight (or only visiblelight irradiation), the standard reduction potentials for which are reported in Table 1.…”
Section: Visible-light-driven Photocatalysismentioning
confidence: 99%
“…Recently, the PEC activity of SrNbO 2 N for water splitting at a neutral pH was largely enhanced via the bottom-up fabrication of the photoanode and the addition of NaCl to an aqueous electrolyte. 29 The feasible mechanism to simultaneously drive the HER and CER using the perovskite oxynitride in artificial seawater is illustrated in Fig. 7(B).…”
Section: Alternative Oxidation Reactions To the Oermentioning
confidence: 99%
“…Vertical SrNbO 2 N nanorod arrays uniformly covered with CoO x nanoparticles presented a photocurrent of 1.3 mA cm –2 at 1.23 V RHE , which is about 2.6 times higher than that of a SrNbO 2 N nanoparticle thin-film electrode . Trinh and Seo reported that SrNbO 2 N/Nb photoanode obtained from bottom-up fabrication exhibited photoelectrochemical seawater-splitting activity for the first time …”
Section: Introductionmentioning
confidence: 98%
“…30 Trinh and Seo reported that SrNbO 2 N/Nb photoanode obtained from bottom-up fabrication exhibited photoelectrochemical seawater-splitting activity for the first time. 31 The works above suggest that the interface construction and surface modification are very important for improving the photocatalytic activity of SrNbO 2 N. Therefore, it is necessary to gain insight into the relationship between the surface structure and physicochemical properties of this semiconductor at the atomic level. Most of the reported theoretical works focused on the crystal structure and electronic, optical, and dielectric properties of bulk SrNbO 2 N. 32−34 In 2016, Umezawa and Janotti theoretically studied the solid solution formed between SrTiO 3 and SrNbO 2 N by constructing the interface model along the [110] direction and analyzed the band offset between the two components.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting is highly promising for solar hydrogen production since it is low-cost, efficient, and clean and can simultaneously produce and separate hydrogen. However, its efficiency is limited by the sluggish water oxidation reaction (WOR). , Tremendous effort has thus been made to identify high-efficiency photoanodes. Hematite (α-Fe 2 O 3 ) holds particular promise since it allows a photocurrent of up to 12.6 mA cm –2 under one-sun irradiation and because it is highly stable in alkaline solution, low-cost, earth-abundant, and environmentally friendly. , Nevertheless, its water oxidation activity (WOA) is largely restricted by low conductivity, short hole diffusion length, high surface-state density, and slow surface oxygen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%